2010
DOI: 10.2320/matertrans.mb200916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shear Strain on the Microstructural Evolution of a Low Carbon Steel during Warm Deformation

Abstract: The microstructural evolution of a low carbon steel was investigated under two different conditions with and without shear strain, using electron backscattered diffraction (EBSD) when a uniaxial compression of 67% was applied at a warm working temperature of 773 K. The equivalent strain and shear strain imposed by the compression test were calculated quantitatively by finite element analysis (FEA). As the equivalent strain was increased without any shear strain, the texture of the and fibers was strongly devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…5(c)), the initial grains in the region near the surface of Al layer were fragmented into the equiaxed fine grains. This indicates that the redundant shear strain plays an important role in grain refinement, which is consistent with the role of shear strain in ultragrain refinement during ARB process of aluminum [50] and IF-steel [52][53][54]. At the same time, the fraction of high-angle boundaries over 15° was up to 68% in the surface region of Al layer.…”
Section: Microstructural Evolution Through the Thickness Of Al Layerssupporting
confidence: 84%
See 1 more Smart Citation
“…5(c)), the initial grains in the region near the surface of Al layer were fragmented into the equiaxed fine grains. This indicates that the redundant shear strain plays an important role in grain refinement, which is consistent with the role of shear strain in ultragrain refinement during ARB process of aluminum [50] and IF-steel [52][53][54]. At the same time, the fraction of high-angle boundaries over 15° was up to 68% in the surface region of Al layer.…”
Section: Microstructural Evolution Through the Thickness Of Al Layerssupporting
confidence: 84%
“…At the same time, the fraction of high-angle boundaries over 15° was up to 68% in the surface region of Al layer. The shear strain introduced by high friction accelerates the grain subdivision, which is similar to the finding by Kang et al [54] in the warm deformation of low carbon steel.…”
Section: Microstructural Evolution Through the Thickness Of Al Layerssupporting
confidence: 69%
“…THERMEC 2013 lubricant which ensures low temperatures are maintained and such annealing phenomena are prevented [15]. Some researchers have reported this fibre to form due to shear deformation [16]. In close agreement to this finding, the present CPFEM predictions have shown that the Φ=0° fibre forms due to biaxial deformation (Fig.…”
supporting
confidence: 83%
“…Inoue et al, 2002 reported that in the ferrite grain transformed from deformed austenite, the grain size in the area with the shear strain is finer than that in the area without the shear strain under the same equivalent plastic strain. Cho et al, 2004;Kang et al, 2010 demonstrated significant advances in high angle grain…”
Section: Discussionmentioning
confidence: 99%